From hair to heart: how to suspect Carvajal syndrome in children. - Sreenivasamurthy, R.H.; Mehta, P.; Doddaiah, N.; Vunnam, V. (European Journal of Pediatric Dermatology, 2025)
Carvajal syndrome is an autosomal recessive disorder due to a defect in the desmoplakin gene. It is characterized by woolly hair, striated palmoplantar keratoderma, and left ventricular cardiomyopathy. While hair and skin features develop during childhood, cardiac symptoms do not appear until adolescence. We describe the case of a 3-year-old boy who presented with cough, fever, vomiting and loose stools, respiratory distress, and tachycardia. Tests revealed arrhythmogenic cardiomyopathy and acute viral myocarditis. The presence of woolly hair and palmoplantar keratoderma raised suspicion of a cardiocutaneous syndrome. Genetic testing revealed a mutation in the desmoplakin gene, leading to the diagnosis of Carvajal syndrome.